Beta-adrenergic receptor activation increases GABA uptake in adolescent mice frontal cortex: Modulation by cannabinoid receptor agonist WIN55, 212-2. (November 2018) - Martins, Robertta Silva; de Freitas, Isis Grigorio; Sathler, Matheus Figueiredo; Martins, Vladimir Pedro Peralva Borges; Schitine, Clarissa de Sampaio; da Silva Sampaio, Luzia; Freitas, Hércules Rezende; Manhães, Alex Christian; dos Santos Pereira, Maurício; de Melo Reis, Ricardo Augusto; Kubrusly, Regina Célia Cussa
Abstract: GABA transporters regulate synaptic GABA levels and dysfunctions in this system might result in psychiatric disorders. The endocannabinoid system (ECS) is the main circuit breaker in the nervous system and may alter noradrenaline (NA) communication, which in turn modulates the release of GABA. However, a close relationship between these systems has not been recognized. We asked whether NA and ECS might control extracellular GABA levels in slices of frontal cortex (FC) of adolescent Swiss mice with 40 days after birth (PN40). Here we show that NA and isoproterenol (ISO), a beta-adrenergic agonist, increased [ 3 H]-GABA uptake in mice FC, while alpha1 -adrenergic agonist phenylephrine had no effect. As GAT-1 is expressed and fully functional at the FC, addition of NO-711, a GAT-1 inhibitor, dose dependently blocked [ 3 H]-GABA uptake. The increase of [ 3 H]-GABA uptake induced by ISO was also blocked by NO-711. [ 3 H]-GABA release induced by 80 mM KCl was reduced by NO-711, but not by removal of Ca 2+ . ISO also increased cyclic AMP (cAMP) levels and addition of WIN 55, 212-2, a mixed CB1 /CB2 receptor agonist, inhibited the effect of ISO in GABA uptake increase, GAT-1 expression and cAMP levels compared to control. Our data show that GABA transport increased by NA and ISO is negatively regulated by cannabinoid receptor agonist WIN55, 212-2. Highlights: Noradrenaline increases [ 3 H]-GABA uptake in adolescent mice Frontal Cortex. The increase of [ 3 H]-GABA uptake induced by isoproterenol (ISO) is blocked by NO-711. [ 3 H]-GABA release induced by 80 mM KCl is reduced by NO-711, but not by removal of Ca 2+ . WIN 55, 212-2 inhibited the effect of ISO in GABA uptake, GAT-1 expression and cAMP levels.